Florida Subtropical Peaches: General Concepts and Cultivars Recommended for Grower Trials - James Ferguson; Peter Andersen; Jose Chaparro; Jeffrey Williamson (EDIS)
HS1125, a 9-page illustrated fact sheet by J. Ferguson, P. Andersen, J. Chaparro, and J. Williamson, discusses general concepts of subtropical production for commercial growers and homeowners and recommends cultivars for grower trials. Includes a table of chilling hours for several Published by the UF Department of Horticultural Sciences, January 2008.